2022
DOI: 10.1186/s12877-022-03135-y
|View full text |Cite
|
Sign up to set email alerts
|

Low physical activity is the strongest factor associated with frailty phenotype and frailty index: data from baseline phase of Birjand Longitudinal Aging Study (BLAS)

Abstract: Background Frailty is the most complicated expression of aging that is related to disability or multi-morbidity. The aim of the present study was to estimate the prevalence of frailty and its associated factors among community-dwelling aged population. Methods A total of 1529 eligible community- dwelling older adults (≥ 60 years) were enrolled in the baseline phase of Birjand Longitudinal Aging Study (BLAS) from 2019 to 2020. Their frailty status w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 58 publications
0
14
0
3
Order By: Relevance
“…It is essential to understand the intensity of daily physical activity of the geriatric population because empirical evidence has shown a very significant role of low physical activity status as the onset of the progression of physical frailty [ 37 , 38 , 39 ]. The Birjand Longitudinal Aging Study (BLAS) has stated that low physical activity is the most important determinant of physical frailty [ 40 ]. Fried (2016) illustrated that “physical activity offers the first evidence of effective approaches to preventing or treating frailty and a biologic model for future therapies” [ 41 ] (p. 11).…”
Section: Discussionmentioning
confidence: 99%
“…It is essential to understand the intensity of daily physical activity of the geriatric population because empirical evidence has shown a very significant role of low physical activity status as the onset of the progression of physical frailty [ 37 , 38 , 39 ]. The Birjand Longitudinal Aging Study (BLAS) has stated that low physical activity is the most important determinant of physical frailty [ 40 ]. Fried (2016) illustrated that “physical activity offers the first evidence of effective approaches to preventing or treating frailty and a biologic model for future therapies” [ 41 ] (p. 11).…”
Section: Discussionmentioning
confidence: 99%
“…Frailty leads to physical deterioration and reduced mobility. Therefore, lacking exercise and motion, the process of muscle degeneration in frail patients would be more severe than in those not [ 25 ]. Martino et al found that intramuscular lipid concentration increased in localized regions of the lumbar muscles following 60-day bed rest [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Physical activity was the lifestyle factor most strongly associated with frailty, especially physical frailty, which is in line with what is described in several studies stating that moderate to vigorous physical activity as well as physical activity at home are protective factors against frailty in older adults [ 34 , 35 ]. Nevertheless, as people age, sedentary behaviour and isolation increase [ 36 , 37 ], which further contributes to frailty [ 38 ]. It is likely that frail people are unable to be physically active owing to real and perceived barriers that represent obstacles to the adoption and maintenance of regular physical activity; however, we should not exclude them from physical activity programs because they are unlikely to adhere and thus it is important to find strategies that motivate them to participate [ 39 ].…”
Section: Discussionmentioning
confidence: 99%